Using Youtube in Training Process Skills Through Student Self-Practice - Fatikhatun Nikmatus Sholihah; Eka Novita Sari (APPLICATION: Applied science in Learning Research, 2022)
The 2013 curriculum prioritizes education in developing student competencies which include knowledge and skills, one of the skills is process skills. The application of process skills with the subject of grade VII, amounting to 15 students in science learning at MTs At-Taufiq Jombang through discovery learning models in independent practicum activities has never been assessed. This study aims to determine the relationship between process skills and student cognitive learning outcomes through the solar system practicum learning. The type of research used in this study is a pre-experimental design with a One-case study, where the test is given after the treatment. Data collection was carried out through interviews, observations, and questionnaires on the performance of students' process skills. The data obtained were then analyzed statistically using the product moment correlation test formula using SPSS 25. The significant value between process skills and cognitive learning outcomes shows the product moment coefficient value is 0.445. Based on these criteria, the relationship between the two variables is not significant. That is, there is no relationship between process skills and student cognitive learning outcomes. However, if it is seen from the correlation value between process skills and learning outcomes, it is obtained a value of 0.214 which means that the relationship is very low (0.20-0.399)